Discharge of rain-storm water in dowelling Areas Constructed on a thick clay strata lacking the rain-water net work system services - Ali Hussein Khudhair (Journal of Madenat Alelem University College, 2018)
In dowelling areas constructed on a thick-clay strata’s lacking the services of rain-water network system, flood is possible in occasions of heavily rain-storms. This research indicates the possibility of discharging the run-off water into the ground through cess-pits. These pits are digged out through the impervious strata to the previous under laid strata where the water infiltrated from